Antibacterial Test of Groundcherry Leaf Extract Liquid Soap Against Staphylococcus Aureus - Febriana F, Mareta; Wibowo, Wibowo; Kurnia Andika , Venny (Riviera Publishing, 2023)
Groundcherry is a medicinal plant with many benefits and properties. Groundcherry leaves contain flavonoid and alkaloid compounds, which can be used as antibacterials. Antibacterial is a substance that can kill or inhibit the growth of bacteria on the skin, such as Staphylococcus aureus, which can cause skin infections. Antibacterial preparations are generally very varied. One type of antibacterial preparation is liquid soap. This research aims to determine whether Groundcherry leaf extract liquid soap preparations can inhibit the growth of Staphylococcus aureus bacteria and to determine the effect of different formulations of Groundcherry leaf extract liquid soap preparations on the ability to inhibit the growth of Staphylococcus aureus bacteria. Liquid soap formulations use extracts with concentrations of 10%, 15% and 20%. The method used in this research was disc diffusion using positive control, negative control and test samples (formulations I, II, III). The research results showed that the liquid soap preparation was able to inhibit bacterial growth. A clear zone in the area around the disc indicated this. Differences in the concentration of extracts in liquid soap preparations can affect bacterial growth. The diameter of the inhibition zone of the formula in the sequence is 10% concentration, the diameter of the inhibition zone is 7.97 mm, and the 15% concentration the diameter of the inhibition zone is 14.82 mm. The 20% concentration, the diameter of the inhibition zone is 17.6 mm, so it can be concluded that the leaf extract liquid soap preparation Groundcherry can inhibit the growth of Staphylococcus aureus bacteria.